2006
DOI: 10.1016/j.jvs.2005.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein 4: Potential regulator of shear stress-induced graft neointimal atrophy

Abstract: Increased BMPs (particularly BMP4) coupled with decreased noggin may promote high shear stress-mediated graft neointimal atrophy by inhibiting SMC proliferation and increasing SMC death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
21
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 62 publications
(82 reference statements)
5
21
1
Order By: Relevance
“…BMP4 mRNA expression was slightly increased by day 1 but significantly increased at 7 days compared to normal flow grafts [13]. We observed a similar time course of Bmp4-lacZ induction in ligated mouse carotid arteries.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…BMP4 mRNA expression was slightly increased by day 1 but significantly increased at 7 days compared to normal flow grafts [13]. We observed a similar time course of Bmp4-lacZ induction in ligated mouse carotid arteries.…”
Section: Discussionsupporting
confidence: 74%
“…For example, Wong failed to demonstrate an effect of rhBMP2 on a human aortic SMC apoptosis after 24 hours [28], while Zhang et al observed increased apoptosis in pulmonary artery SMCs harvested from patients with primary pulmonary hypertension and treated with rhBMP2 for 48 hours [32]. Increased SMC apoptosis has recently been demonstrated in baboon neointimal cells exposed to rhBMP4 but only after 48 and 72 hours [13]. It is also possible that the effects of BMPs on SMC apoptosis are transduced through other signaling mechanisms that do not involve Alk-3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of BMP2 and/or BMP4 in endothelial cells is significantly increased under various endothelial injurious conditions, including high flow shear stress (16), oscillatory shear stress (41), hyperhomocysteinemia (49), or treatment with H 2 O 2 (41), tumor necrosis factor-␣ (41), or hypoxia (5). The increased expression of BMPs under some of these conditions was found to mediate an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies report that VSMCs mainly localize in the distal region of the vascular stenosis with low shear stress [128][129][130]. Increasing blood flow in vessel grafts induces endothelialization and inhibits neointimal hyperplasia [125,131], the molecular mechanism of which is based on the high expression of bone morphogenic proteins (BMP4) [132] and NO [123]. However, segments of the artery wall exposed to lower endothelial shear stress are significantly thicker than segments exposed to higher shear stress within the same artery [133].…”
mentioning
confidence: 99%